Main content

### Course: Pre-algebra > Unit 15

Lesson 3: Solving systems with substitution- Systems of equations with substitution: 2y=x+7 & x=y-4
- Systems of equations with substitution
- Systems of equations with substitution: y=4x-17.5 & y+2x=6.5
- Systems of equations with substitution: -3x-4y=-2 & y=2x-5
- Systems of equations with substitution: 9x+3y=15 & y-x=5
- Systems of equations with substitution
- Systems of equations with substitution: y=-5x+8 & 10x+2y=-2
- Systems of equations with substitution: y=-1/4x+100 & y=-1/4x+120
- Substitution method review (systems of equations)

© 2024 Khan AcademyTerms of usePrivacy PolicyCookie Notice

# Systems of equations with substitution: -3x-4y=-2 & y=2x-5

Learn to solve the system of equations -3x - 4y = -2 and y = 2x - 5 using substitution. Created by Sal Khan.

## Want to join the conversation?

- why would we be shown up by talking birds? please help!(83 votes)
- In a former video, an evil advice-giver dude was humiliated by a smart talking bird. How Sal came up with that, I have no freaking clue.(62 votes)

- Every time there is a video about systems of equations with substitution there is always 2 equations. Could you find the values of x and y (if you had 2 unknown variables) with only one equation?(19 votes)
- If you have one equation with 2 variables (or a linear equation like 2x + 5y = 20), there are an infinite set of solutions. This type of equation creates a line where each point on the line represents an (x, y) ordered pair that is a solution to the equation.

When you have 2 equations with the same 2 variables, then you have a system of linear equations. The solution to the system is the point (or points) that the 2 linear equations have in common.

Hope this helps.(51 votes)

- i get how to solve for y but how do you solve for x(12 votes)
- just plug in the value of y into one of the original equations and solve for x(16 votes)

- I am experiencing brain fog. I have a test tmrw. Any advice??(8 votes)
- It’s okay to study the night before the test, but don’t stay up too late studying. It is best to get a good night’s sleep before the test.(27 votes)

- 00:03…. um..…. question mark?(9 votes)
- In a former video, a king's advisor was humiliated by a smart talking bird who can do math.(14 votes)

- what is 2x=16-8y but you have to substitute x+4y=25 how would you do this(5 votes)
- To substitute, you have two choices to isolate variables, in both equations, solving for x is the easiest. In the first equation, you could divide by 2 to get x=8-4y. If you have 8-4y+4y=25, you end up with 8=25, so there is no solution (lines parallel).

If you subtract 4y in second equation, you get x=25-4y and substituting in first gives 2(25-4y)=16-8y, distribute to get 50-8y=16-8y, so when you add 8y to both sides, 50=16 which also gives no solution.

This can be seen by getting both in slope intercept form:

y=-1/4 x + 2 and y=-1/4 x + 25/4, both have same slope and different intercepts.(8 votes)

- What would 250m = pc be? (p and c are both variables)(7 votes)
- What are other ways of solving systems of equations?(4 votes)
- When substitution method is taught, you are usually also taught the elimination method and graphing methd.

In later classes in Algebra, you would also learn how to use matrices to solve systems of linear equation.(6 votes)

- what about something like this:

43x+6y=87

20x-2y=74

I need to find what x and what y is. I am stuck. Can anyone explain how to do these problems please?

Thanks(4 votes)- 43x+6y=87

43x+6y+−6y=87+−6y(Add -6y to both sides)

43x=−6y+87

43x/43 = -6y+87/43

x=-6/43y + 87/43

Subsitute -6/43y + 87/43 for x in 20x-2y=74

20x-2y=74

20(-6/43y+87/43)-2y=74

-206/43 y+1740/43 = 74 ( simplify both sides of the equation)

-206/43 y +1740/43 + -1740/43 =74=-1740/43 (add(-1740)/43 to both sides)

-206/43 y = 1442/43 ( divide both sides)

y=-7

Subsitute

x=-6/43 y+87/43

x=-6/43(-7)+87/43 ( simplify)

x=3

x=3 and y=-7(6 votes)

- How do you get rid of the Y in an equation like this

2x + 3y = 0

x + 2y = - 1(4 votes)- This video is about substitution. Are you trying to solve for "y" so you can substitute? Or, are you trying to do elimination method rather than substitution?

If you need to use substitution method, it would be easier to solve for "x" in the 2nd equation: x = -2y-1. Then substitute it into the first equation to solve for "y".

If you are using elimination method, again - there is less work if you elect to eliminate "x". Multiply the 2nd equation by -2. Then, add the 2 equations. If you really want to eliminate "y", then you need to manipulation both equations. Multiply the first equation by 2 and multiply the 2nd equation by -3. Then, add the 2 equations.

Hope this helps.(5 votes)

## Video transcript

So that it's less likely that we get shown up by talking birds in the future, we've set a little bit of exercise for solving systems of equations with substitution. And so this is the first exercise or the first problem that they give us. -3x-4y=-2 and y=2x-5 So let me get out my little scratch pad and let me rewrite the problem. So this is -3x-4y=-2 and then they tell us y=2x-5. So, what's neat about this is that they've already solved the second equation. They've already made it explicitly solved for y which makes it very easy to substitute for. We can take this constraint, the constraint on y in terms of x and substitute it for y in this first blue equation and then solve for x. So let's try it out. So this first blue equation would then become -3x-4 but instead of putting a y there the second constraint tells us that y needs to be equal to 2x-5. So it's 4(2x-5) and all of that is going to be equal to -2. So now we get just one equation with one unknown. and now we just have to solve for x. So, let's see if we can do that. So, it's -3x and then this part right over here we have a -4, be careful, we have a -4 we want to distribute. We are going to multiply -4*2x which is -8x and -4*-5 is positive 20 and thats going to equal -2. And now we can combine all the x terms so -3x-8x, that's going to be -11x and then we have -11x+20=-2. Now to solve for x, we'll subtract 20 from both sides to get rid of the 20 on the left hand side. On the left hand side, we're just left with the -11x and then on the right hand side we are left with -22. Now we can divide both sides by -11. And we are left with x is equal to 22 divided by 11 is 2, and the negatives cancel out. x = 2. So we are not quite done yet. We've done, I guess you can say the hard part, we have solved for x but now we have to solve for y. We could take this x value to either one of these equations and solve for y. But this second one has already explicitly solved for y so let's use that one, so it says y = 2 times and instead of x, we now know that the x value where these two intersect, you could view it that way is going to be equal to 2, so 2 * 2 - 5 let's figure out the corresponding y value. So you get y=2(2)-5 and y = 4 - 5 so y = -1. And you can verify that it'll work in this top equation If y = -1 and x=2, this top equation becomes -3(2) which is -6-4(-1) which would be plus 4. And -6+4 is indeed -2. So it satisfies both of these equations and now we can type it in to verify that we got it right, although, we know that we did, so x=2 and y=-1. So, let's type it in... x=2 and y=-1. Excellent, now we're much less likely to be embarassed by talking birds.